Brønsted acid‐catalyzed polymerization of ε‐caprolactone in water: A mild and straightforward route to poly(ε‐caprolactone)‐graft‐water‐soluble polysaccharides. Issue 15 (7th June 2014) - Stanley, Nicholas; Bucataru, Georgiana; Miao, Yong; Favrelle, Audrey; Bria, Marc; Stoffelbach, Francois; Woisel, Patrice; Zinck, Philippe
ABSTRACT The polymerization of ε‐caprolactone (ε‐CL) has been assessed in water using various Brønsted acids as catalysts. The reaction was found to be quantitative at 100 °C, leading to number–average molecular weights up to 5000 g mol−1. The Brønsted acid‐catalyzed polymerization of ε‐CL in water was further conducted in the presence of water‐soluble polysaccharides thereby affording graft copolymers. The approach enables an easy, mild access to dextran hydroxyesters. For low degree of substitution, the latter self‐assembles in water to form nanoparticles. Poly(ε‐CL)‐graft‐methylcellulose copolymers can also be obtained via a similar approach. It is noteworthy that the methodology reported herein is a one‐step route to poly(ε‐CL)‐graft‐water‐soluble polysaccharides, operating in mild conditions, that is, at low temperatures, using readily available metal‐free catalysts and water as a solvent. © 2014 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2014, 52, 2139–2145